Utilization of non-prescription medicines in minor ailments management: A nationwide study undertaken among Malaysian community pharmacists - Boon Seng Tan, Angel Wei Ling Goh, Chee Ping Chong (Journal of Applied Pharmaceutical Science, 2020)
The absence of dispensing separation between private doctor clinics and pharmacies is the main challenge of the Malaysian community pharmacists. Within this context, the utilization of non-prescription medicines for minor ailments treatment is one of the major roles of the pharmacists. This study aimed to evaluate the minor ailments management using non-prescription medicines among the Malaysian community pharmacists. This was a cross-sectional descriptive study. The entire population of Malaysian community pharmacists (n = 2,730) were invited for participation. Data were collected across the first 10 requests for minor ailments management involved adult consumers in a working day. A total of 173 pharmacists were participated (response rate 6.3%) and 1,704 consumers with 2,149 minor ailments were encountered. The consumers mostly have one minor ailment (78.3%) and involved acute conditions (92.3%). Productive cough (7.3%), fever (6.3%), and dermatitis (6.1%) were most commonly managed by the pharmacists. Cetirizine (5.9%), paracetamol (4.7%), and diclofenac (4.2%) were most frequently dispensed and each consumer received an average (median) of two medications. The median duration of treatment was 5 days [inter-quartile range (IQR): 3–7] and the cost of treatment involved only medicines cost (median: RM 13.40; IQR: 8.00–21.00) without any consultation fee. The majority of the consumers (75.5%) sought help from pharmacists first without consulting the doctors. Only 16.4% of the consumers were followed-up by the pharmacists. In conclusion, the pharmacists actively managed the minor ailments with an affordable cost of treatment. Guidelines and an audit system should be established to enhance the minor ailments practices of the pharmacists.
Keywords: Community pharmacist, minor ailments, non-prescription medicines, cost.